Information Technology for Classification of Donosological and Pathological States Using the Ensemble of Data Mining Methods - Kryvova, O.A.; Kozak, L.M. (Cybernetics and computer engineering, 2021)
The purpose of the paper is to develop information technology for the classification of human health states using an set of Data Mining methods and to carry out its validation on examples of a operators` functional state and patient's disease severity. Results. The developed IT unites several stages: I — data pre-processing; II — clustering, selecting the homogeneous groups (data segmentation); III — predictors` identification; IV — classifying the studied states, development of predictive models using machine learning algorithms (Decision trees, Support vector machines, neural networks) and the method crossvalidation. The proposed IT was used to classify the operators` functional statе and the patients` severity in case of disease progression.